The first Brazilian municipal initiative of payments for environmental services and its potential for soil conservation - Zolin, C. A.; Folegatti, M. V.; Mingoti, R.; Paulino, J.; Sanchez-Roman, R. M. [UNESP]; Gonzalez, A. M. O. [UNESP] (Elsevier B.V., 2014)
It has become evident that policies aimed at mitigating the growing water resources and water use conflicts in Brazil are crucial. The municipality of Extrema in Minas Gerais state in Brazil pioneered the first Brazilian municipal PES initiative (Conservador das Aguas program), based on the relationship between forests and the benefits they provide. This study aimed to assess soil loss in the Posses sub-basin, where the Conservador das Aguas program began. Additionally, we aimed to determine the potential that this PES initiative has for soil conservation, as well as to minimize the soil losses as a function of forest area size and location in order to propose a technical approach for implementing PES. In this sense, considering the prescribed conservation practices, land use situation, and soil cover in the Posses sub-basin, we analyzed the effectiveness of the Conservador das Aguas program before and after implementation in relation to reduced soil loss under 36 different land use and soil cover scenarios. We used a geographic information system (GIS) for spatializing and producing different information plans and the Revised Universal Soil Loss Equation (RUSLE) for estimating soil loss. As a result, we found that minimization of soil loss may be obtained by adopting pasture conservation practices. Additionally the expected average soil loss in the Posses sub-basin under conditions of land use and soil cover, before and after implementing the water conservation program was 30.63 and 7.06 Mg ha(-1) year(-1), respectively. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Sustainability; Soil conservation; Water conservation program; Land cover